Nest-mounds of the yellow meadow ant (Lasius flavus) at the "Alter Gleisberg", Central Germany: Hot or cold spots in nutrient cycling?. (January 2015) - Bierbaß, Peggy; Gutknecht, Jessica L.M.; Michalzik, Beate
Abstract: Nests of the yellow meadow ant ( Lasius flavus ) occur at high densities in grasslands worldwide. Although many studies have shown that L . flavus nests influence soil nutrient contents, little is known about their effect on soil nutrient cycling rates. The aim of this study was to examine the role of nest-mounds inhabited by L. flavus as potential 'hot spots' for soil nutrient cycling. Six pairs of nest-mounds and control soils were selected at a grassland site at the plateau of the Alter Gleisberg (Thuringia, Central Germany). L. flavus significantly modified the soil environment within the nest. In comparison to the control soils, nest-mounds were characterized by slightly higher soil temperatures during the summer months. In addition, we found that nests were related to decreased potential C mineralization rates and increased potential net N mineralization rates. Nest-mound soil exhibited lower amounts of SOC, hot-water extractable DOC and DN, and higher concentrations of leachable DOC and DN. Moreover, ants promoted the enrichment of base cations in the nest. Differences in the soil environment between nests and control soils were possibly a result of the burrowing activity of ants, soil mixing, accumulation of aphid honeydew, and decreased plant-derived nutrient inputs into the nest-mound soil. In conclusion, L. flavus nest-mounds had a significant but element dependent effect on the soil nutrient cycling and may represent cold spots for C cycling and hot spots for N cycling. Thus, L. flavus nests increase the spatial heterogeneity of soil properties and create unique micro-sites within grassland ecosystems. Highlights: We hypothesize that Lasius flavus nests act as 'hot spots' for soil nutrient cycling. L. flavus had a significant but element dependent effect on nutrient cycling. Differences were likely due to soil mixing, honeydew accumulation and low plant-derived nutrient input.